Sahara - Eisner, Breck; McConaughey, Matthew, 1969-; Zahn, Steve, 1968-; Cruz, Penélope.; Wilson, Lambert; Wilson, Rainn, 1966-; McGarvey, Seamus, 1967-; Mansell, Clint; Cussler, Clive; Paramount Home Entertainment (Firm) ([Hollywood, Calif.] : Paramount Home Entertainment, 2005)
Master explorer Dirk Pitt and his wisecracking sidekick, Al Giordino go on the adventure of a lifetime while seeking out a lost Civil War battleship known as the 'Ship of Death'.
Based on the novel by Clive Cussler.
Special features: Commentary by Breck Eisner; commentary by Breck Eisner and Matthew McConaughey; 3 featurettes; deleted scenes.
Director of photography, Seamus McGarvey ; editor, Andrew MacRitchie ; music, Clint Mansell ; costume designer, Anna Sheppard ; production designer, Allan Cameron.
Matthew McConaughey, Steve Zahn, Penelope Cruz, Lambert Wilson, Rainn Wilson, Lennie James, Glynn Turman, Paulin E. Fodouop, Patrick Malahide, Delroy Lindo.
MPAA rating: PG-13; for action violence.
DVD, widescreen presentation; Dolby Digital 5.1 and 2.0.
Keywords: Pitt, Dirk -- (Fictitious character) -- Drama; Battleships -- Drama; United States -- History -- Civil War, 1861-1865 -- Drama; Feature films; Films for the hearing impaired